1998
DOI: 10.1159/000030314
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transurethral Prostate Resection and Transurethral Laser Prostatectomy on Plasma Hormone Levels

Abstract: Objective: The short and long-term effects of two common transurethral procedures (TURP and TULP, transurethral prostatic resection and laser prostatectomy, respectively) on plasma hormone levels in patients with benign prostatic hyperplasia (BPH) have been evaluated. Patients and Methods: Totally 57 patients with histologically proven BPH (age range 54–81 years, mean 62.5 years) were included into the study program. Of these 57 patients, 44 underwent TURP and 13 underwent TULP for treatment of their bladder o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…In patients undergoing TURP and transurethral laser prostatectomy, there was a significant increase in LH concentrations 3 weeks after the procedure. However, after 3 months' follow‐up, LH concentrations returned to the normal range, indicating a possible effect of the prostate gland on these hormones . The present study underscores the demonstration of negative feedback from the removal of the whole prostate gland on the hypothalamic–pituitary–testicular axis.…”
Section: Discussionsupporting
confidence: 67%
“…In patients undergoing TURP and transurethral laser prostatectomy, there was a significant increase in LH concentrations 3 weeks after the procedure. However, after 3 months' follow‐up, LH concentrations returned to the normal range, indicating a possible effect of the prostate gland on these hormones . The present study underscores the demonstration of negative feedback from the removal of the whole prostate gland on the hypothalamic–pituitary–testicular axis.…”
Section: Discussionsupporting
confidence: 67%
“…In the patients who received TULP, only the plasma LH levels were significantly increased at the 3-month time point relative to the preoperative time point. Therefore, Kadir Türkölmez et al, considered that some factors released from the resected prostate gland may have affected the evaluation results and that the differences may be related to a higher amount of residual prostate tissue after TULP [20]. Furthermore, previous observational studies have reported no changes in testosterone, LH, FSH, adrenocorticotropic hormone, or dehydroepiandrosterone sulfate levels at short-term (3 weeks) [21] and 3-month follow-up time points after surgery [20].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Kadir Türkölmez et al, considered that some factors released from the resected prostate gland may have affected the evaluation results and that the differences may be related to a higher amount of residual prostate tissue after TULP [20]. Furthermore, previous observational studies have reported no changes in testosterone, LH, FSH, adrenocorticotropic hormone, or dehydroepiandrosterone sulfate levels at short-term (3 weeks) [21] and 3-month follow-up time points after surgery [20]. In the present study, we noted a significant difference between preoperative and postoperative testosterone levels in the low-testosterone group (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Certain studies have shown that there are no significant changes in these hormones following surgical treatment for benign prostatic hyperplasia (BPH) (12,16,17). Further investigations are required, but on the basis of these studies it appears that BPH does not significantly affect the hypothalamic-pituitary axis.…”
Section: Discussionmentioning
confidence: 99%